Game Edukasi Hafalan Surat Pendek Al-Qur’an The Adventure Of Ali - Vadlya Maarif; Hidayat M. Nur; Fitrian Chandrayoga (Indonesian Journal on Software Engineering (IJSE), 2020)
Abstract: Games at this time become a very popular thing, even early childhood have played games using an Android smartphone. But children tend to play games excessively, that causing concerns for parent about the negative effects of games that affect their children. Therefore the game "The Adventure of Ali" was created which is a game with an educative concept and is a game as a learning media or educational game. Education itself is very broad in scope, ranging from formal and non-formal education. Memorizing short Al-Qur'an surah is an education that is classified as non-formal, which is non-formal education sometimes tends to be excluded from formal education. So from that the game is made for memorizing short Al-Qur'an surah media, in the form of puzzles in the game. “The Adventure of Ali“ is an educational game for memorizing short Al-Qur'an surah that is packaged in adventure and puzzle games that will make children learn without realizing he is learning.Keywords: Games Education, Adventure, Puzzles, Memorizing Short Al-Qur'an Surah, Children, ParentsAbstrak: Game pada saat ini menjadi hal yang sangat popular, bahkan anak-anak usia dini-pun sudah bermain game menggunakan telepon pintar Android. Tapi anak-anak cenderung bermain game dengan berlebihan sehingga menimbulkan kekhawatiran bagi orang tua terhadap efek negatif dari game yang berdampak pada anaknya. Oleh sebab itu dibuatlah game “The Adventure of Ali” yang merupakan game dengan konsep edukatif dan merupakan game sebagai media pembelajaran atau game edukasi. Edukasi sendiri sangatlah luas cakupannya, mulai dari edukasi formal dan non-formal. Menghafal surat pendek Al-Qur’an merupakan suatu edukasi yang tergolong non-formal, yang dimana edukasi non-formal terkadang cenderung tersisih dibandung edukasi formal. Maka dari itu game dibuat untuk media hafalan surat pendek Al-Qur’an berupa puzzle yang ada dalam game. “The Adventure of Ali” merupakan game edukasi hafalan surat pendek Al-Qur’an yang dikemas dalam game petualangan dan puzzle yang akan membuat anak belajar tanpa menyadari dirinya sedang belajar.Kata kunci: Game Edukasi, Petualangan, Puzzle, Hafalan Surat Pendek Al-Qur’an, Anak-Anak, Orang Tua